PENERAPAN SWEDISH MASSAGE UNTUK MENURUNKAN TEKANAN DARAHPADA PENDERITA HIPERTENSI DI PUSKESMAS PAMPANG MAKASSAR - Kristina Wisrance; Akbar Asfar; Andi Mappaanganro; Brajakson Siokal (CV. Adiba Aisha Amira, 2025)
BackgroundHypertension, or high blood pressure, is one of the most common public health problems worldwide. It is known as the